The use of Robotics for the Development of Social Skills for Children with ASD - Kouloumenta, Stavroula; Drigas, Athanasios (Technium Education and Humanities, 2022)
This paper researches an innovative technology in the field of ICT (robotics) to support the cultivation of social skills in children with ASD (Autistic Spectrum Disorder), as these have been documented internationally in recent years.